This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 1 − x ) − n = 1 + n x + 2 ! n ( n + 1 ) x 2 + ⋯ + r ! n ( n + 1 ) ( n + 2 ) ⋯ ( n + r − 1 ) x r + ⋯ ∞ terms
1 + 4 3 + 4 ⋅ 8 3 ⋅ 5 + 4 ⋅ 8 ⋅ 1 2 3 ⋅ 5 ⋅ 7 + ⋯
⇒ T r + 1 = 4 r × r ! 3 ⋅ 5 ⋅ 7 ⋯ ( 2 r + 1 )
⇒ T r + 1 = 2 r × r ! 3 ⋅ 5 ⋅ 7 ⋯ ( 2 r + 1 ) × 2 r 1
⇒ T r + 1 = r ! 2 3 ⋅ 2 5 ⋅ 2 7 ⋯ 2 ( 2 r + 1 ) × ( 2 1 ) r
⇒ T r + 1 = r ! 2 3 ⋅ ( 2 3 + 1 ) ⋅ ( 2 3 + 2 ) ⋯ ( 2 3 + r − 1 ) × ( 2 1 ) r
Comparing with the above written binomial expansion , we get that the expression in the question is basically the expansion of ( 1 − x ) − n where x = 2 1 , n = 2 3
So our answer is 2 2